Recognition of the Type of Cesarean Scar Pregnancy in First Trimester Sonography. (January 2023) - Fernandez, Carlos M.; Levine, Elliot M.; Shashoua, Abraham; Sodini, Irma; Duval, Jude; Juna, Jacqueline
This case series is presented to illustrate the clinical value of identifying, sonographically, the type of cesarean scar ectopic pregnancy that may present, as this has become more frequently encountered. The choice of surgical treatment appears to be dependent on the sonographic typing, of this specific type of ectopic pregnancy. This case study illustrates the importance of this topic, given the rising incidence of cesarean deliveries coupled with the increase in first trimester sonograms being more commonly performed. The value of proper diagnostic detection is important, given the contemporary management of this new type of ectopic pregnancy.